Analysis of the Price of Summary Water Disposal at the Kampung Kasai Derawan Islands Berau District - Wahananto, Anang; Witjaksana, Budi; Patriadi, Andi (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2024)
Raw water is water that can be derived from surface water sources, groundwater reservoirs and/or rainwater that is used as raw water for drinking water. Raw water that has passed through a process with a certain intake system and is stored in as clean water and when continued with the process of the Drinking Water Supply System (SPAM) then will produce water ready for use by the community. The presence of clean water in a region becomes very important given the very dynamic community activity. To meet the need for clean water, the population of a region can rely on water from direct water sources such as surface water and rainwater because both sources of water are easily accessible even though most of them are polluted either directly or indirectly by human activity itself. Therefore, an in-depth analysis of effective clean water management strategies is needed to address the shortage of supply during the rainy season in the villages. Research methods carried out using a cost estimate analysis of clean water supply. The pumping tests were conducted continuously for a certain time and when the pumping test was felt sufficient, where the groundwater surface position was relatively stable at a certain depth, then the pump was shut down. In the case of the 24 hour pumping testing, a constant flow of 2.32 Lt/second was obtained.